EFEKTIVITAS EKSTRAK DAUN LAMTORO (Leucaena leucocephala) TERHADAP DAYA VERMISIDAL Fasciola sp - Baiq Marlianti; Mashur; Candra Dwi Atma; Katty Hendriana Priscilia Riwu (JURNAL SANGKAREANG MATARAM, 2024)
Fasciolosis is a parasitic disease that affects ruminant animals and often causes losses among farmers in the form of decreased livestock productivity, even leading to death in animals. This disease is caused by an infection of Fasciola sp. parasites. This study aims to determine the vermicidal effect of Leucaena leucocephala leaf extract on Fasciola sp. in vitro, based on the duration of death. The samples used in this study were Fasciola worms taken from the Majeluk Slaughterhouse. This research used a Completely Randomized Design (CRD) with 7 treatments and 3 replications. The treatments in this study consisted of Leucaena leucocephala leaf extract at concentrations of 2.5%, 3.5%, and 4.5%. Albendazole at concentrations of 2.5%, 3.5%, and 4.5%, and negative control using distilled water. The data obtained were analyzed using analysis of variance (ANOVA), and further tested using Duncan's test. The results of this study showed that Leucaena leucocephala leaf extract treatments at concentrations of 2.5%, 3.5%, and 4.5% had significantly different effects (P > 0.05) in accelerating the death time of Fasciola sp. compared to the negative control (distilled water), but still lower than the Albendazole treatment. Administration of Albendazole, even at the lowest concentration (2.5%), caused faster death of the worms compared to Leucaena leucocephala leaf extract